Saudi Arabia : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This staff report on Saudi Arabia's 2013 Article IV Consultation discusses economic policies and development. As the largest crude oil exporter, and the only producer with significant spare capacity, Saudi Arabia plays a systemic and stabilizing role in the global oil market. In 2011, Saudi Arabia formally committed through the G20 to use its systemic position in the oil market to promote global stability. Saudi Arabia raised oil production to a 30-year high to ensure demand was met the abrupt decline in Libyan production in 2011, and continued geopolitical tensions in 2012. Growth in fiscal spending has contributed to continued robust growth in private-sector credit of more than 16 percent, and high levels of liquidity in the banking system.